The Mediating Role of Brand Trust on the Effect of Customer Experience and Engagement on Brand Loyalty: A Lesson From Bukalapak - Wijaya, Natalia Rebecca Audrey; Simamora, Bilson (AIBPM Publisher, 2023)
Intense competition among marketplaces in Indonesia caused Bukalapak traffic to decline significantly from 2019 to 2022 amid the growing number of @bukalapak Instagram followers. The authors believe that this decline is related to brand loyalty. Academic works stated that customer experience and engagement influence brand loyalty. However, brand trust mediation on that influence has not been thoroughly investigated. Therefore, this study aims to identify how brand trust mediates the effect of customer experience and engagement on Bukalapak brand loyalty. To satisfy that aim, the researchers judgmentally recruited 210 followers ofÂ @bukalapak Instagram account as the sample. Using Structural Equation Modeling (SEM) with WarpPLS version 8.0 for data analysis, the research found that customer experience and engagement positively influence brand trust. Subsequently, customer experience, customer engagement, and brand trust positively impact brand loyalty. Mediation analysis shows that brand trust mediates customer experience and customer engagement effect on brand loyalty. However, in this research, the researchers has not considered to used other social media besides Instagram. Future research can make the same study in different social media, such as Facebook or Twitter.